Cysteine proteases from bloodfeeding arthropod ectoparasites - Sojka, Daniel; Francischetti, Ivo M B; Calvo, Eric; Kotsyfakis, Michalis (Advances in experimental medicine and biology, 2011)
Cysteine proteases have been discovered in various bloodfeeding ectoparasites. Here, we assemble the available information about the function of these peptidases and reveal their role in hematophagy and parasite development. While most of the data shed light on key proteolytic events that play a role in arthropod physiology, we also report on the association of cysteine proteases with arthropod vectorial capacity. With emphasis on ticks, specifically Ixodes ricinus, we finally propose a model about the contribution of cysteine peptidases to blood digestion and how their concerted action with other tick midgut proteases leads to the absorbance of nutrients by the midgut epithelial cells.
Keywords: Parasites; Animals; stravovací zvyklosti; klíšťata; členovci; zvířata; paraziti; Arthropods; Ticks; Feeding Behavior; Cysteine Proteases; Culicidae; cysteinové proteasy